Zimbabwe tourism destination brand positioning and identity through media: A tourist's perspective - Chigora, Farai; Ndlovu, Joram; Zvavahera, Promise (Goodwood Publishing, 2021)
Purpose: The study was based on understanding how media can be used to select Zimbabwe tourism destination brands against other brands by the tourists. Further, it examined the role of media in improving Zimbabwe tourism brand identity. Factors to use in positioning the Zimbabwe tourism brand were also established. Research Methodology: A quantitative to the qualitative sequential mixed method was used to get research data. The respondents and participants to the study were tourism operators, media organizations and tourists (n=452). Results: The study's findings informed that tourism and media organizations in Zimbabwe are failing to understand the best ways to use media to attract tourists. There was a significant disagreement in the views of tourists and organizations, especially based on choosing a tourism destination brand using media. Even on improving Zimbabwe tourism destination brand identity and positioning, both parties agreed that media could help improve brand identity. Limitations: Getting opinions and views of tourists is difficult considering the divergence in their perceptions. A mixed-methods could help in improving objectivity. Contribution: The study, therefore, recommended an intensive tourism media audit, considering media as a strategic brand identity tool and a nationwide survey to come up with brand positioning elements specifically for Zimbabwe tourism destinations.